AB1091 Tolerability of vaccination of 13 pcv in patients with jia, without systemic manifestations. (12th June 2018) - Alexeeva, E.; Dvoryakovskaya, T.; Soloshenko, M.; Denisova, R.; Isaeva, K.; Mamutova, A.; Mayansky, N.; Tkachenko, N.; Zubkova, I.; Kaluzhnaya, T.; Gayvoronskaya, A.; Broeva, M.; et al.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is one of the most frequent and most disabling rheumatic diseases in children. Children with JIA receiving immunosuppressive and genetically engineered biologic drugs belong to the high-risk group for the development of bacterial and viral infections, including those administered by preventive vaccines. Objectives: Our aim was to evaluate the tolerability of the pneumococcal 13-valent conjugate vaccine (PCV) in children with JIA. Methods: In a prospective cohort study, 3 groups were formed: children with JIA in the remission phase on methotrexate or etanercept (group I), with JIA in the active phase prior to the appointment of methotrexate or etanercept (group II), control group (conditionally healthy children). 0.5 ml of the 13-valent PCV was administered once subcutaneously during therapy in patients in the remission phase or 3 weeks before the appointment of methotrexate or etanercept in patients in the active phase. Results: At this stage of work, the tolerability of the 13 PCV vaccine was evaluated in patients with JIA, without systemic manifestations. In our study, the post-vaccination period was asymptomatic in 58% of the children in Group I, 66% in children in Group II, and in 60% in the control group. Most often in the postvaccinal period, local reactions were noted, which were painful at the place of administration of the vaccine in 6% of the children in group I, 8% in group II, and 24% in the control group, respectively. Less developed oedema and hyperemia at the injection site – in 12% of children in group I, 6% in group II, in 8% of children in the control group. There was no significant difference in the incidence of local reactions to vaccination of 13 PKV in patients with JIA and in children of the control group. Analysis of the time of occurrence and duration of local and systemic reactions to vaccination of 13 PKV showed that the maximum severity of symptoms was noted in the first day, by the 2–3 day of observation, complaints and fever disappeared. The increase in local reactions was noted 2 days after immunisation, followed by extinction to 3–4 days of follow-up. There were no serious adverse events in the post-vaccination period. Conclusions: Vaccination with the 13-valent PCV in children with JIA is safety and is not accompanied by the development of serious adverse events. Disclosure of Interest: E. Alexeeva Grant/research support from: Roche, Pfizer, Centocor, Novartis, T. Dvoryakovskaya Grant/research support from: Roche, Pfizer, M. Soloshenko: None declared, R. Denisova: None declared, K. Isaeva: None declared, A. Mamutova: None declared, N. Mayansky: None declared, N. Tkachenko: None declared, I. Zubkova: None declared, T. Kaluzhnaya: None declared, A. Gayvoronskaya: None declared, M. Broeva: None declared, M. Fedoseenko: None declared